Bounded rationality in decision making: Biases in managers of the Portuguese port sector - Jordão, A. R. F.; Costa, R. L. da.; António, N. J. dos S.; Falcão, P. F. (XXIX Jornadas Hispano-Lusas de Gestión Científica - Emprendimiento, estrategia y conocimiento, 2019)
Decision-making is a multidisciplinary and ubiquitous phenomenon in organizations, and it can be observed at the individual, group, and organizational levels. Decision making plays, however, an increasingly important role for the manager, whose cognitive competence is reflected in his ability to identify potential opportunities, to immediately detect and solve the problems he faces, and to predict and prevent future threats. Nevertheless, to what extent do managers of the most diverse sectors continue to rely on false knowledge when they have better strategies at their disposal? The present article proposes the diagnosis of three prominent biases – overconfidence, optimism, and anchoring effect – in managers of the Portuguese port sector, as well as a comparative analysis with the conclusions already documented in relation to the Brazilian civil construction sector. In addition, this paper also provides a set of measures capable of contributing to the mitigation of the effects of these and other biases.